1996
DOI: 10.1086/289971
|View full text |Cite
|
Sign up to set email alerts
|

Science and Core Knowledge

Abstract: While endorsing Gopnik's proposal that studies of the emergence and modification of scientific theories and studies of cognitive development in children are mutually illuminating, we offer a different picture of the beginning points of cognitive development from Gopnik's picture of “theories all the way down.” Human infants are endowed with several distinct core systems of knowledge which are theory-like in some, but not all, important ways. The existence of these core systems of knowledge has implications for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0
12

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(137 citation statements)
references
References 45 publications
3
122
0
12
Order By: Relevance
“…Babies believe that agents are distinct from objects in that they can move without contact (Spelke, Phillips, & Woodward, 1995) and act in certain ways in response to goals (Woodward, 1998;Gergely & Csibra, 2003). Confronted with evidence that children's behavior is restricted in predictable ways, the natural response is to hypothesize the existence of innate constraints, including the whole object constraint (Markman, 1990) core systems of object representation, psychology, physics, and biology (Carey & Spelke, 1996;Spelke & Kinzler, 2007;Carey, 2009), and so on. Given that they appear so early in development, it seems sensible to postulate that these constraints are innate rather than learned.…”
Section: Acquiring Inductive Constraintsmentioning
confidence: 99%
“…Babies believe that agents are distinct from objects in that they can move without contact (Spelke, Phillips, & Woodward, 1995) and act in certain ways in response to goals (Woodward, 1998;Gergely & Csibra, 2003). Confronted with evidence that children's behavior is restricted in predictable ways, the natural response is to hypothesize the existence of innate constraints, including the whole object constraint (Markman, 1990) core systems of object representation, psychology, physics, and biology (Carey & Spelke, 1996;Spelke & Kinzler, 2007;Carey, 2009), and so on. Given that they appear so early in development, it seems sensible to postulate that these constraints are innate rather than learned.…”
Section: Acquiring Inductive Constraintsmentioning
confidence: 99%
“…Dzieci uczą się liczyć już w wieku trzech lat -zaczynają od odnoszenia liczebników do konkretnych przedmiotów lub działań (Blakemore i Frith, 2008). Carey i Spelke (1996) wskazały, że dzieci w tym wieku mają trudności z wykonaniem zadania, w którym muszą porównać dwa (lub więcej) zbiory przedmiotów, ale jeśli zadanie dotyczy jednego zbioru przedmiotów, to radzą sobie z jego wykonaniem i rozumieją, że liczenie ma stały porządek, a o wielkości zbioru decyduje ostatnia policzona wartość. Nie są to jednak zaawansowane zdolności liczenia.…”
Section: Krytyka Koncepcji Zmysłu Liczbyunclassified
“…To support this claim of innateness, emotion researchers, like researchers in cognitive development (e.g., [13]), demonstrate that very young infants have emotion concepts. For example, Izard and colleagues have demonstrated that children as young as 2.5 months express interest, joy, sadness and anger [59].…”
Section: Integration Completedmentioning
confidence: 99%
“…Many theorists would now argue that at least some mental structures are innate and largely invariant across the lifespan [12,13]. Generally, these 'core knowledge' faculties are thought of as supports for reasoning and knowledge acquisition in certain domains of knowledge; for example, both infants and adults have a core system for estimating how many objects are in a scene [14], as well as a core system for representing and tracking objects [15].…”
Section: Cognitive Development As a Theoretical Approachmentioning
confidence: 99%